2022
DOI: 10.3390/life12060908
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Joint Disk Displacements in Class II Malocclusion and Cervical Spine Alterations: Systematic Review and Report of a Hypodivergent Case with MRI Bone and Soft Tissue Changes

Abstract: (1) Background: This study aimed to perform a literature review related to disk displacement (DD) in class II malocclusion or cervical vertebrae position alterations and to report a hypodivergent case with cervical pain and right anterolateral DD with reduction, left anterolateral DD with reduction, and left joint effusion. (2) Methods: A structured electronic search was conducted between March 2022 and April 2022, without time limits, following PRISMA guidelines, in the following databases: PubMed, Scopus, Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Regarding some aspects that justify Class II treatment such as increase attractiveness [4,5] and consequently self-esteem, helping prevention or assist in the treatment of spinal column problems [6][7][8]10], TMD treatment [26], they are not analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding some aspects that justify Class II treatment such as increase attractiveness [4,5] and consequently self-esteem, helping prevention or assist in the treatment of spinal column problems [6][7][8]10], TMD treatment [26], they are not analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Besides esthetic commitment there are some another significant problem that class II malocclusion brings to the individual. Almasan et al [6] reported a relationship between class II malocclusion, temporomandibular disorders and cervical posture in studies that show MRI bone and soft tissues change, although literature still shows contradictory opinions. Sandoval et al [7] described the relation between retrognathia and cervical lordosis and Zokaite et al [8] reported an increase of cervical inclination and head upright position.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of dental malocclusion can produce temporomandibular disorders (TMDs) [ 22 ]. TMDs commonly refer to a category of musculoskeletal conditions that affect the health of the temporomandibular joint (TMJ), masticatory muscles, and other tissues [ 23 , 24 ]. TMD prevalence in pediatric patients varies significantly, with estimates ranging between 4.2% and 68%, depending on the population under investigation and the assessment method employed [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in craniocervical alignment may contribute to the development and progression of TMJ dysfunctions. [2][3][4][5][6] A review study has shown that there may be a correlation between cranio-cervical postures, such as cranio-cervical angulation, incorrect alignment of the first (C1) and second cervical vertebrae (C2), and temporomandibular joint (TMJ) dysfunction. 5,6 The reciprocal relationship between head posture and jaw function involves the stomatognathic triad, including occlusion, temporomandibular joint and the neuromuscular system.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] A review study has shown that there may be a correlation between cranio-cervical postures, such as cranio-cervical angulation, incorrect alignment of the first (C1) and second cervical vertebrae (C2), and temporomandibular joint (TMJ) dysfunction. 5,6 The reciprocal relationship between head posture and jaw function involves the stomatognathic triad, including occlusion, temporomandibular joint and the neuromuscular system. 7 Skeletal pattern, head posture and TMD's connection remain controversial, although physical and functional connections between the cranial area, temporomandibular joint, cervical spine and hyoid bone have been established.…”
Section: Introductionmentioning
confidence: 99%